Rediscovery of the nearly extinct longnose harlequin frog Atelopus longirostris (Bufonidae) in Junín, Imbabura, Ecuador - Tapia, Elicio (2017)
We report the recent finding of four adults of Atelopus longirostris, a Critically Endangered species that was last seen in 1989, when catastrophic Atelopus declines occurred. The rediscovery of A. longirostris took place in a new locality, Junín, 1250–1480 m asl, Provincia Imbabura, Ecuador, on 28–31 March 2016. The four frogs were found in two isolated small patches of native forest in a fragmented area heavily modified for agriculture and livestock; one patch protected by the Junín Community Reserve, and another non-protected private patch near the reserve. We found high prevalence of Batrachochytrium dendrobatidis (Bd) in the amphibian community of Junín, but A. longirostris tested negative. The finding of A. longirostris after 27 years is surprising and fits an apparent pattern of mild conditions that might be promoting either the recovery or persistence in low numbers of some relict amphibian populations. The frogs are the first founders of an ex situ assurance colony in Jambatu Research and Conservation Center. Expansion of the Junín Community Reserve is urgently needed to add the currently non-protected patch of forest, where A. longirostris also occurs. The restoration of the forest in degraded areas between both forest patches and in the related river margins is also necessary. This restoration will grant the connectivity between both isolated metapopulations and the normal movement of individuals to the breeding sites in the Chalguayacu and Junín River basins. The latter should be protected to prevent any kind of water pollution by the opencast copper exploitation of the mining concession Llurimagua, which is underway. Atelopus longirostris belongs to a group of at least 29 species of Ecuadorian Atelopus that are critically endangered, 15 of which remain unsighted for at least one decade, and most of them might be extinct. Further synchronous, multidisciplinary and integrative research is needed, aiming to understand the most aspects of the biology of species of Atelopus to support in situ and ex situ conservation actions. © 2017, © 2017 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.